2014
DOI: 10.1017/s1751731113002449
|View full text |Cite
|
Sign up to set email alerts
|

Influence of source and micronization of soya bean meal on growth performance, nutrient digestibility and ileal mucosal morphology of Iberian piglets

Abstract: The effects of inclusion in the diet of different sources of soya bean meal (SBM) on growth performance, total tract apparent digestibility (TTAD) and apparent ileal digestibility (AID) of major dietary components and mucosal ileum morphology were studied in Iberian pigs weaned at 30 days of age. From 30 to 51 days of age (phase I), there was a control diet based on regular soya bean meal (R-SBM; 44% CP) of Argentina (ARG) origin and five extra diets in which a high-protein soya bean meal (HP-SBM; 49% CP) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Individual samples of digesta (approximately 20 g) were collected at the terminal ileum (last 2.0 m of the small intestine), freeze-dried, homogenized using a pestle and a mortar, and stored in airtight containers at +4°C until chemical analyses. The apparent ileal digestibility (AID) of DM, OM, GE, and CP were determined as described by Berrocoso et al (2014). For the study of the mucosal structure, a 5-cm section of the middle part of the ileum was dissected in all pigs used for the AID study.…”
Section: Experiments 1: Clean Barnmentioning
confidence: 99%
“…Individual samples of digesta (approximately 20 g) were collected at the terminal ileum (last 2.0 m of the small intestine), freeze-dried, homogenized using a pestle and a mortar, and stored in airtight containers at +4°C until chemical analyses. The apparent ileal digestibility (AID) of DM, OM, GE, and CP were determined as described by Berrocoso et al (2014). For the study of the mucosal structure, a 5-cm section of the middle part of the ileum was dissected in all pigs used for the AID study.…”
Section: Experiments 1: Clean Barnmentioning
confidence: 99%
“…Pelleting and extrusion methods offer several advantages in animal feed production, including improved feed digestibility, reduced ingredient segregation, enhanced pellet durability, and decreased microbial contamination. By processing feed ingredients through pelleting or extrusion, feed manufacturers can achieve greater feed consistency, nutrient retention, and performance benefits for animals, contributing to overall feed efficiency and health outcomes (9,10).…”
Section: Extrusion Techniquementioning
confidence: 99%
“…Graph 2 Changes in in vitro digestibility of soybean, field peas and barley grain after after the micronization and flaking (% d.m.) Berrocoso et al (2014) found that due enhancements in ileal mucosal morphology and nutrient digestibility the use of added value soy products such as micronized soybean meal or soy protein concentrate in diets for healthy pigs weaned at 30 days of age is advised.…”
Section: "1st International Symposium On Biotechnology" Proceedings 2023mentioning
confidence: 99%